IDENTIFICATION OF ORANGE PESTS USING THE METHOD CERTAINTY FACTOR - Mustopa Husein Lubis; Akhir Abadi Tanjung (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Pests are a major problem for citrus farmers, until now the pests that attack citrus plants vary widely. One of the pests on citrus plants is the trunk beetle where this pest attacks the old leaves on the lower branches or branches as a result of which the leaves fall and the young branches die. For this reason, an expert system was designed to identify pests in citrus plants The method used in this research is the certainty factor method. The results based on the symptoms experienced by the citrus plants showed that the pests affected on the citrus plants were Aphids with an expertise level of 0.8 and a percentage of 80% and had a fairly good aquaculture value.            Keywords: citrus plant pest; certainty factor; expert system  Abstrak: Hama merupakan masalah utama bagi para petani jeruk, hingga saat ini hama yang menyerang tanaman jeruk sangat bervariasi. Salah satu hama pada tanaman jeruk adalah kumbang belalai dimana hama ini menyerang daun tua pada ranting atau dahan bagian bawah akibatnya daun gugur dan ranting muda mati. Untuk itu dirancang suatu sistem pakar mengidentifikasi hama tanaman jeruk. Metode yang digunakan pada penelitian kali ini ialah metode faktor kepastian (CF),. Hasil bedasarkan gejala-gejala yang dialami oleh tanaman jeruk tersebut bahwa hama yang terkena pada tanaman jeruk adalah Kutu Daun dengan tingkat kepakaran 0,8 dan persentase 80 % dan memiliki nilai akuasi yang cukup baik. Kata kunci: faktor kepastian; hama tanaman jeruk; sistem pakar;